PENGARUH ACCELERATED LEARNING (PEMBELAJARAN CEPAT) TERHADAP KETERAMPILAN MENULIS PARAGRAF NARASI OLEH SISWA KELAS X SMA NEGERI 10 MEDAN TAHUN PEMBELAJARAN 2012/2013 - AYU WIRA ANGGRAINI (Basastra, 2013)
This study aimed to investigate the effect of Accelerated Learning (Quick Learning) to paragraph narrative writing skills class X SMA Negeri 10-year field study 2012/2013. The population of this study were all students of class X SMA Negeri 10 field consists of 6 classes with a student population of 242 people. Of the number of students was drawn randomly sample 76 students. The method used in this study is an experimental method to design research group posttest only design (two groups) comparing two groups, the experimental group were given learning to write narrative paragraphs Accelerated Learning approach (Quick Learning) while the control group using Expository Teaching (Teaching indirectly) in learning to write narrative. The instrument used is a narrative essay writing test. The average value of the experimental class was 79.42 while the control class is 68.73. Thus it can be said that the average value of the test write narrative paragraphs in the experimental class higher than the control class. Hypothesis testing is done by using the test "t". Test hypotheses derived from calculations thitung = 4.14, then consulted with TTable at the level of 5% and 1% with dk = (N1 + N2) - 2 = (38 + 38) - 2 = 74, then obtained acquired significance level of 5% = 2.00 and a significance level of 1% = 2.65. After consultation, it was to the TTable obtained greater than the 2.00 <4.14> 2.65, then the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted. Keywords: skill, writing paragraph narrative, Approaches Accelerated Learning